Assessment of quality of life and selected aspects of physical, psychological, social, and environmental functioning in patients treated for breast cancer 5 years after breast-conserving surgery or mastectomy - Tarkowska, Magdalena; Głowacka-Mrotek, Iwona; Nowikiewicz, Tomasz; Gastecka, Agata; Szymańska, Justyna; Hagner, Wojciech; Zegarski, Wojciech (Journal of Education, Health and Sport, 2019)
Introduction: Breast cancer is the most common cancer in women in well-developed countries. Modern treatment for breast cancer is multimodal, with surgery being the mainstay of treatment. The aim of the study was to assess quality of life, self-efficacy, and satisfaction with life in patients treated for breast cancer with two different surgery types. Materials and methods: This study involved 360 women – 120 after mastectomy (MAS), 120 after breast-conserving surgery (BCT), and 120 healthy controls (CG). The standardized WHOQOL-BREF (abbreviated form) questionnaire, General Self-Efficacy Scale (GSES), and Satisfaction with Life Scale (SWLS) were used for measuring quality of lifeResults: As regards physical, psychological, social, and environmental functioning (WHOQOL-BREF), women after mastectomy had the worst scores (p<0.001). We did not find any differences between the studied groups with regard to self-reported general health and general quality of life. The scores in GSES and SWLS were lowest among patients after mastectomy, whereas the BCT and CG groups did not differ significantly in this respect. Conclusions: Mastectomy, which is necessary in some patients with breast cancer, significantly impairs quality of life. Regardless of the time that has passed since surgery, different patients need different kinds of support, including psychological care.